Pesquisa de Salmonella sp. em aves criadas em sistema industrial e alternativo - Alcântara, Juliana Bonifácio de (2015)
Salmonella sp. might cause food deseases in humans and it be isolated from the gastrointestinal tract of different animal species, especially birds. In this study, we aimed to point out the main characteristics of non-conventional poultry farm systems at Central and South regions of the State of Goiás and to determine the frequency of Salmonella sp. Isolation in conventional and non-conventional poultry farms, as well as the frequency of positivity for antigen-antibody reaction at non-conventional poultry farms. On paper 1, we studied 190 non-conventional systems of broiler rearing; we collected 3,040 blood and organ samples (heart, liver, crop and cecum) from 760 birds. Rapid Plate Agglutination Test was used for the detection of anti-Salmonella sp. antibodies in blood serum, and conventional bacteriology and biochemistry tests were used for bacterium culture and isolation. Data on the characteristics of the properties were obtained through medical records. The poultry rearing systems were classified as semi-intensive (49.0%) and extensive (42.6%). In these breeding systems, 48.0% were of specific breed free-range chickens and 42.0% of rustic rustic free-range chickens; 74.2% of the farms had commercial purpose. The frequency of properties with chicken seropositive to the anti-Salmonella sp. antigen was 16.3%, and 12.0% of the samples. Salmonella was detected in 4.7% of the properties and the identified serotypes were Anatum, Infantis, Mbandaka, Schwarzengrund and Panama. For Paper 2, we studied 44 flocks of chickens from nine poultry slaughterhouses, three with over 51,000 birds slaughtered/day and six with up to 50,000 birds slaughtered/day. On the slaughter line 1,232 organ samples and feathers were harvested. A total of 21 feather samples and 21 samples of each organ (spleen, crop and cecum) was collected, both of them were analyzed by conventional bacteriology and biochemistry tests. The organ samples were processed in groups of three, in a total of seven samples of each organ. Of the 44 flocks of chickens, 22 were positive for Salmonella. The feathers presented a higher positivity frequency (12.3%). The spleen presented the highest frequently of isolates (8.1%). The frequency of positive samples in both crop and cecum was 3.8%. Among 88 Salmonella isolates, the serovars Schwarzengrund (29.5%), Agona (25.2%), Mbandaka (12.6%), Anantum (8.0%) and Infantis (3.4%) were predominant. In conclusion, the non-conventional designs are characterized as semi-intensive, and use improved lineage of chickens for commercial purposes. Regardless of the levels of contamination, Salmonella sp. is present in chickens from both conventional and non-conventional production systems. The pathogen was identified in greater numbers in chicken organs at conventional farm. In non-conventional breeding samples, Salmonella sp. isolation was low, but the number of seropositive chickens was higher. The serovars identified in samples of both conventional and non-conventional systems were similar, and some of relevance to public health.